Analisis Dan Perancangan Sistem Informasi Fasilitas Sekolah - Ahmad Jacky (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
System can be defined as interconnected elements in order to complete a task. Moreover, there are four components that are need to be involved to develop a system. These four elements are input, process, output and control. With the development of technology nowadays, it gives significant benefits in problem solving fields including problems in educational fields in this case junior high school. Based on our observation and interview with the stakeholders of SMP Negeri 2 Airmadidi, we decided to design an information system that covers the school’s facilities which are the library and the school’s medication unit. The current system is not computerized. Therefore, using structured analysis which is the Data Flow Diagram this study aim to develop a system that can be implemented in the future.